Lactose intolerance: An update on its pathogenesis, diagnosis, and treatment - Catanzaro, Roberto; Sciuto, Morena; Marotta, Francesco (Nutrition research (New York, N.Y.), 2021)
Lactose intolerance has a high prevalence worldwide, ranging between 57% and 65%. It is caused by a reduction or loss of the activity of the intestinal enzyme lactase−phlorizin hydrolase, responsible for the digestion of lactose. This alteration determines an increased osmotic load in the small intestine and the fermentation of lactose by the bacterial flora, which leads to a high production of short-chain fatty acids and gas. This is followed by the onset of abdominal pain, diarrhea, and flatulence. In addition to these problems, it was found that subjects with lactose intolerance have an increased risk of developing various extra-intestinal diseases, including cancers. The diagnosis is essential to undertake an adequate treatment and, for this purpose, different methods have been tested. These include genetic test, hydrogen breath test (HBT), quick lactase test, and lactose tolerance test. HBT is the most used method because it is non-invasive, inexpensive, and highly sensitive and specific, as well as easy to perform. In clinical practice, the other methods are mainly used as HBT integration tests. There are also many therapeutic options. An appropriate intervention concerns the dietetic style, such as the consumption of lactose−free foods, but with nutritional characteristics comparable to dairy products. Other valid choices are represented by the use of exogenous enzymes, probiotics, prebiotics, the selection of milk containing specific types of beta−caseins. This review is intended to illustrate the diagnostic methods currently available and the possible therapeutic options for lactose intolerance.